Optimization of asymmetrical magnetic lenses with the aid of EOD program - Kadhem, Wasan J.; Naser, Ban A.; Abbas, Talib M. (International Journal of Engineering & Technology, 2018)
A common method used for the design of magnetic lenses is the analysis optimization procedure that using the finite element method with the aid of the Munro programs. The latter way has been applied in the present work to investigate asymmetrical magnetic lenses in conjunction with Electron Optical Design software( EOD). The influence of two important geometrical parameters, namely the axial bore diameter and the air gap, on the objective and projector properties. Our results show that all of the optical properties has been studied minutely are improved at the lowest values of these two parameters.